2021
DOI: 10.1021/acsomega.1c00480
|View full text |Cite
|
Sign up to set email alerts
|

Green Electrospun Membranes Based on Chitosan/Amino-Functionalized Nanoclay Composite Fibers for Cationic Dye Removal: Synthesis and Kinetic Studies

Abstract: Chitosan/poly(vinyl alcohol)/amino-functionalized montmorillonite nanocomposite electrospun membranes with enhanced adsorption capacity and thermomechanical properties were fabricated and utilized for the removal of a model cationic dye (Basic Blue 41). Effects of nanofiller concentrations (up to 3.0 wt %) on the morphology and size of the nanofibers as well as the porosity and thermomechanical properties of the nanocomposite membranes are studied. It is shown that the incorporation of the nanoclay particles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…Evaluations of surface charge by zeta potential (Figure 3c) have determined that the Clay-MOF composite is positively charged at all pH values (3)(4)(5)(6)(7)(8)(9)(10)(11). The surface charge gradually decreased from + 10.2 mV at pH 5 down to + 0.93 mV at pH 11.…”
Section: Dye Adsorption Performancementioning
confidence: 97%
See 2 more Smart Citations
“…Evaluations of surface charge by zeta potential (Figure 3c) have determined that the Clay-MOF composite is positively charged at all pH values (3)(4)(5)(6)(7)(8)(9)(10)(11). The surface charge gradually decreased from + 10.2 mV at pH 5 down to + 0.93 mV at pH 11.…”
Section: Dye Adsorption Performancementioning
confidence: 97%
“…Therefore, surface modification and/or hybridization of clay‐based adsorbent are vital issues for efficient wastewater treatment. Several attempts have also been conducted on the preparation of functionalized and composite clay structures with different materials such as dendritic nanostructures, [6] calcium alginate, [5] chitosan, [7,8] and nanoparticles [9] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reusability is one of the crucial economic indexes for evaluating the industrial application of adsorbents. 45 Therefore, the stability and regeneration performance of the synthesized MIIP were studied through adsorption-desorption cycle tests. Briefly, 20 mg MIIP was dispersed in 50 mL 20 mg L À1 Rb + solution (pH = 10), and when the adsorption process was at equilibrium, MIIP was separated using an external magnet.…”
Section: Reusabilitymentioning
confidence: 99%
“…Nanoparticles based on clay minerals, have received extensive attention due to their remarkably low-cost, large abundance, high specific surface area, and good intrinsic adsorption characteristics [11,23,31]. Because of the anionic nature of the clay nanoparticles in aqueous media, a number of studies have been reported the efficacy of clay minerals for removing cationic dyes from wastewater [41,42]. Bentonite (Bent) is a naturally occurring clay that is composed tetrahedral Si layer and octahedral Al layer which are interlinked and contain reactive -OH groups.…”
Section: Introductionmentioning
confidence: 99%